Further development of a cell culture based approach to model the diet-derived impacts on the faecal microbiome and potential host health in the domestic dog : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy (Ph.D.) in Animal Science at Massey University, Palmerston North, New Zealand - Phimister, Francis (Massey University, 2023)
Globally, diets that promote and optimise health and a ‘healthy microbiome’ are becoming increasingly popular for pets. However, the impacts of novel diet ingredients and formulations on the health of the host and their microbiome require testing to ensure there are no unforseen detrimental effects. However, there are currently a very limited number of canine-specific intestinal cell lines and the capacity to utilise these cells to model host-food interactions is limited. Thus, this doctoral project aimed to develop an in vitro model of the canine intestine, using a previously established canine intestinal epithelial cell (cIEC) line. This could then be used to characterise the canine response to dietary challenges to the gut microbiota. As there is limited research that has assessed the interactions of the gut microbiota with the canine intestine, the initial step of this project was to evaluate the current knowledge of the intestinal inflammatory response to bacterial ligands and diet-derived metabolites (Chapter Two). This literature review indicated that prior to investigating the interactions between bacteria and the canine intestine an evaluation of the canine intestinal response to these challenge compounds was required. Building on the knowledge base established in Chapter Two, key microbes associated with health in the dog required identification. Thus, this thesis provided the first meta-analysis of the available literature on the relationship of dietary nutrients and their impact on the gut microbiota in the dog (Chapter Three). The hypothesis of this meta-analysis was that dietary protein and dietary fats would have singificant impacts on the faecal microbiota of the dog and additionally, that this analysis would reveal bacterial genera associated with these dietary macronutrients.In the meta-analysis the novel discovery was made that despite its low relative abundance,Sharpea was the genera most associated with causing the shifts in microbial profiles in response to changes in both crude protein, and crude fats, thus confirming the hypotheses. Early results indicated that the methods required to further refine the existing cIEC line as an in vitro model of the canine intestine were sub-optimal and required further development. These method developments are detailed in Chapter Four. Experiments in this chapter assessed methods to promote cell growth and differentiation in a cellZscope system, which automatically performed barrier integrity assessments, whilst inside a temperature-controlled incubator. The inclusion of 150 nM hydrocortisonein cell culture media during the initial 48 hours of cellular differentiation, and subsequent removal of hydrocortisone after this period successfully enabled the cIEC to differentiate and form confluent monolayers in the cellZscope system. These methods were intended to be used going forwards in an apically anaerobic system that would more closely resemble conditions seen in vivo and would have allowed the simultaneous culture of the oxygen-requiring cIEC and anaerobic bacteria. Work utilising this model was stopped due to complications that arose from the Covid-19 pandemic, but work conducted and experiments that were planned are explored in Chapter Six. Utilising the refined methods from Chapter Four, the inflammatory response of the cIEC to butyrate and bacterial lipopolysaccharides (LPS) were characterised (Chapter Five). This was performed to address gaps in the literature highlighted in Chapter Two.It was hypothesised that the stimulation with bacterial LPS would cause a pro-inflammatory response, whilst the stimulation with butyrate would cause an anti-inflammatory response. Furthermore, it was also hypothesised that the stimulation of the cIEC with both LPS and butyrate would cause the butyrate to reduce the pro-inflammatory response, and the LPS to reduce the anti-inflammatory response. It was observed that LPS induced a pro-inflammatory response in the cIEC, which butyrate was able to mitigate in most instances. Overall, the methods developed and refined in this project will be able to be utilised in future experiments utilising these cells, such as evaluating new pet food ingredients for beneficial effects and exploring how changes in the gut microbiome impact gut health in the dog. It can take the knowledge established in Chapter Three to further investigate the impacts of the bacterial genera on the health of the dog. Futhermore, it can utilise the immune responses observed in Chapter Five to better understand the relationship between inflammation and diet in the dog. Future work can build on the knowledge discovered and presented in this thesis to fully understand the impact of diet changes on the health of the dog, and further define the microbial profile of the ‘healthy microbiome’ for the dog
Keywords: Dogs; Nutrition; Digestive organs; Toxicity testing; In vitro; Cell culture; Technique; Microbiology; Cultures and culture media; 300903 Veterinary bacteriology